Retreat in real time—Nantucket’s balancing act along a changing coast - McKaye, Devon J.; Murphy, Vincent; Hill, Leah (Frontiers in Climate, 2025)
Nantucket, an island about 30 miles off the coast of Massachusetts, has long embraced retreat in response to coastal hazards. This community case study examines how Nantucket is enhancing its resilience by adapting to increasing coastal storms, erosion, and sea level rise through strategic retreat and relocation. Nantucketers have historically moved structures such as lighthouses and homes away from the coastline, but the increasing frequency and intensity of storms demand more comprehensive and adaptable solutions. Through resilience planning and policy efforts, the Town of Nantucket is addressing these challenges by balancing short- and long-term objectives, public and private interests, and equity considerations. Lessons learned from Nantucket’s experiences are applicable to other communities facing similar coastal risks, highlighting the importance of strategic planning, community support, and capacity building for effective retreat and relocation.